Sistem Informasi Pengelolaan Data Keuangan Parkiran Berbasis Website : (Studi Kasus Cv Pramudita) - Natanial Landu Amah; Fajar Hariad; Murry Albert Agustin Lobo (STIKes Ibnu Sina Ajibarang, 2024)
Pramudita is a company that operates in the field of parking lot management services at one of the Regional General Hospitals in East Sumba, where CV. Pramudita still records manually in a book, namely recording financial data in the form of income and expenditure of parking financial data every day, so there are often errors in recording financial data. CV. Pramudita needs a financial data management system to help store financial data in the form of daily income and expenses and also various issues that include financial matters. The system design that will be designed includes a website-based financial information system. This system was also built using the waterfall method with PHP, HTML and MySQL programming languages. From the SUS test results, this parking financial data management information system is included in the marginal category, acceptability ranges and high, the scale grade obtained is D and the level of user satisfaction is OK.